Opening the Conversation: study protocol for a Phase III trial to evaluate a couple-based intervention to reduce reproductive and sexual distress among young adult breast and gynecologic cancer survivor couples - Jessica R. Gorman; Karen S. Lyons; S. Marie Harvey; Chiara Acquati; John M. Salsman; Deborah A. Kashy; Julia H. Drizin; Ellie Smith; Lisa M. Flexner; Brandon Hayes-Lattin; Jennifer B. Reese (Trials, 2022)
Abstract Background Reproductive and sexual health (RSH) concerns are common and distressing for young adults diagnosed with breast and gynecologic cancer and their partners. This study evaluates the efficacy of a virtual couple-based intervention called Opening the Conversation (OC). The OC intervention is grounded in theory and evidence-based practice and was adapted to improve coping and communication specifically in relation to RSH concerns after cancer. Methods This Phase III trial is conducted in a fully remote setting and enrolls young adult couples (current age 18–44 years) with a history of breast or gynecologic cancer (stage 1–4, diagnosed under age 40) within the past 6 months to 5 years. Eligible dyads are recruited from across the USA. The target sample size is 100 couples. Dyads are randomly assigned to receive either the 5-session OC intervention or a 4-session active control intervention (Side by Side). The primary outcomes are change in reproductive distress and sexual distress. Secondary outcomes include communication about reproductive concerns, communication about sexual concerns, depressive symptoms, sexual function, relationship quality, relationship intimacy, sexual satisfaction, self-efficacy to communicate about sex and intimacy, and quality of life. An exploratory aim examines whether dyadic coping and communication quality mediate intervention effects on survivors’ and partners’ reproductive distress or sexual distress. Self-report outcome measures are assessed for both groups at baseline (T1), 2 weeks post-treatment (T2), and 3 months post-treatment (T3). Discussion Despite the importance of RSH for quality of life for young adult cancer survivors and their partners, evidence-based interventions that help couples navigate RSH concerns are lacking. This randomized controlled trial will determine the efficacy of a novel couple-based intervention to reduce distress related to RSH concerns for younger couples after breast or gynecologic cancer, in comparison to an active control intervention. Trial registration ClinicalTrials.gov NCT04806724. Registered on Mar 19, 2021.